Financial Performance: Big Data & Sustainabiity Competitive Advantage Studi Kasus Institusi Keuangan di Indonesia - Muchlis, Muchlis (SUSTAINABLE JURNAL AKUNTANSI, 2023)
ABSTRACT This research aims to determine the extent to which big data can influence financial performance in the world of industry, both directly and mediated by competitive advantage. This research uses secondary data on financial institutions listed on the Indonesia Stock Exchange, totaling 23 institutions. Data is processed using robust regression with the Least Time Square (LTS) estimator. The results of this research show that there is a significant positive influence between big data and financial performance, both directly and mediated by competitive advantage. Keywords: Big Data, Competitive Advantage, Financial Performance